2019
DOI: 10.1093/schbul/sbz029
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Retinal Cytoarchitectural Abnormalities in Schizophrenia and Bipolar Disorder

Abstract: Background Schizophrenia (SZ) and bipolar disorder (BD) are characterized by reductions in gray matter and white matter. Limitations in brain imaging have led researchers to use optical coherence tomography (OCT) to explore retinal imaging biomarkers of brain pathology. We examine the retinal layers that may be associated with SZ or BD. Methods Articles identified using PubMed, Web of Science, Cochrane Database. Twelve studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 43 publications
4
51
0
Order By: Relevance
“…The high sMRI correlation between SCZ and BD is consistent with prior reports of sMRI similarities between the two disorders (26). Moreover, a large body of literature reports substantial etiologic overlap between the two disorders (27)(28)(29)(30)(31). Because of such data, the SCZ and BD have been described as sharing a continuum of etiology leading to psychotic (32), neurophysiological (32) and neurocognitive (33) symptoms.…”
Section: Discussionsupporting
confidence: 84%
“…The high sMRI correlation between SCZ and BD is consistent with prior reports of sMRI similarities between the two disorders (26). Moreover, a large body of literature reports substantial etiologic overlap between the two disorders (27)(28)(29)(30)(31). Because of such data, the SCZ and BD have been described as sharing a continuum of etiology leading to psychotic (32), neurophysiological (32) and neurocognitive (33) symptoms.…”
Section: Discussionsupporting
confidence: 84%
“…Also, the relative sparing of the RNFL was found predominantly in the temporal quadrant in patients with PD, and in the superior and inferior RNFL quadrants in patients with AZ [35]. According to a meta-analysis, there was significant with a moderate effect size thinning of the RNFL for the global and nasal region in the patients with SZ and BD [14]. Another study found significant thinning of the nasal parafoveal RNFL in SZ compared to HC, but not in the overall or temporal region [41].…”
Section: Discussionmentioning
confidence: 99%
“…Initial applications of OCT were limited mainly to ophthalmic diseases, but several studies found that the changes of the neural layers of the retina might predict CNS pathology such as cortical atrophy with patients in many non-ocular diseases [11,12]. Similarly, several studies on OCT tested the progression of the psychiatric disorders and found the thinning of RNFL or macula in patients with schizophrenia (SZ) [13], bipolar disorder (BP) [14], major depression (MD) [15], and anorexia nervosa [16]. However, the retinal findings were not strongly correlated with clinical symptoms in major psychiatric diseases [10].…”
Section: Introductionmentioning
confidence: 99%
“…Our study findings have important implications. Retinal vascular abnormalities bear relation to abnormalities in RNFL thickness, which in turn is related to brain abnormalities seen in SCZ and BD . Fundus photography is relatively inexpensive when compared to OCT or neuroimaging.…”
Section: Discussionmentioning
confidence: 99%